Temporal Injustice in Aviation Emissions: A New Paradigm for LCA Accountability - Bahman, Nahed (Journal of Environmental Accounting and Management, 2026)
Aviation emissions present a dual challenge, their significant contribution to global greenhouse gas accumulation and the uneven distribution of their impacts across present and future generations. Current life cycle assessment (LCA) approaches often overlook the temporal dimension of these impacts, resulting in an incomplete basis for climate policy decisions. To address this gap, the Temporal Emissions Weighting Factors (TEWFs), a new metric that assigns dynamic value to emissions based on their future climate impact, is developed and applied. Using a hub-and-spoke airport system as a case study, the paper reveals how emissions differ not only by class and route structure but also in their temporal burden, disproportionately affecting future populations. The integration of TEWFs into LCA marks a shift from static carbon accounting to a dynamic, justice-sensitive approach that considers both the timing of emissions and their unequal impacts across generations. By embedding ethical temporal weighting, the framework enhances impact precision while aligning LCA with principles of intergenerational equity and climate justice. The paper also proposes a graphical methodological framework to operationalize TEWFs in aviation assessments. Results show that TEWF-adjusted metrics significantly alter the distribution of emissions responsibility, offering clear pathways for equitable climate policy and sustainable aviation planning. This research calls for an evolution in LCA standards to include intergenerational ethics and supports global efforts to align aviation sustainability with long-term climate justice goals.